Genome Size, Molecular Phylogeny, and Evolutionary History of the Tribe Aquilarieae (Thymelaeaceae), the Natural Source of Agarwood - Farah, Azman H.; Lee, Shiou Yih; Gao, Zhihui; Yao, Tze Leong; Madon, Maria; Mohamed, Rozi (Frontiers in Plant Science, 2018)
The tribe Aquilarieae of the family Thymelaeaceae consists of two genera, Aquilaria and Gyrinops, with a total of 30 species, distributed from northeast India, through southeast Asia and the south of China, to Papua New Guinea. They are an important botanical resource for fragrant agarwood, a prized product derived from injured or infected stems of these species. The aim of this study was to estimate the genome size of selected Aquilaria species and comprehend the evolutionary history of Aquilarieae speciation through molecular phylogeny. Five noncoding chloroplast DNA regions and a nuclear region were sequenced from 12 Aquilaria and three Gyrinops species. Phylogenetic trees constructed using combined chloroplast DNA sequences revealed relationships of the studied 15 members in Aquilarieae, while nuclear ribosomal DNA internal transcribed spacer (ITS) sequences showed a paraphyletic relationship between Aquilaria species from Indochina and Malesian. We exposed, for the first time, the estimated divergence time for Aquilarieae speciation, which was speculated to happen during the Miocene Epoch. The ancestral split and biogeographic pattern of studied species were discussed. Results showed no large variation in the 2C-values for the five Aquilaria species (1.35 to 2.23 pg). Further investigation into the genome size may provide additional information regarding ancestral traits and its evolution history.